The Development of E-Commerce Web Analytics for BB Master Baby Products Trading - Beh, Kah Kheng; Ibrahim, Noraini (Applied Information Technology And Computer Science, 2023)
In parallel with the increasing demand for baby products in the world market, it is the right time for baby product companies to undoubtedly gain the most beneficial benefit of online shopping in comparison to traditional establishments with precisely set operating hours. A baby product retailer named BB Master Baby Products Trading encountered some problems in its business, including the need for customers to buy products from its only physical store, a small selling area, low service quality and poor business decisions. Thus, an e-commerce website is developed driven by waterfall methodology and employing courier service and Google Analytics API. It allows stakeholders to login, manage profile settings orders, reviews, products, shopping carts, and generate web analytic reports. The testing outcome demonstrates that all website features function well. In conclusion, this website has the potential to aid companies in increasing their marketability and assisting them in making sound business decisions.